2019
DOI: 10.1016/j.urology.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms Associated With Long-term Double-J Ureteral Stenting and Influence of Biofilms

Abstract: All procedures performed involving human participants were in accordance with the ethical standards of the institutional and national research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards. Informed consent Informed consent was obtained from all individual participants included in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Therefore, we determined the in vivo antibacterial activity through evaluating the risk of bacteriuria. In comparison to permanent implant materials, the constantly degrading surface of JQ alloy could completely inhibit biofilm formation, and therefore reducing most of the complications related to peri-infections [ 7 , 17 ]. In an examination of antimicrobial activities of biodegradable magnesium based materials, Nguyen et al [ 19 ] identified several possible mechanisms of antimicrobial activity that may occur as a single activity or in tandem, including oxidative stress, interruption of quorum sensing processes, and changes in Ca 2+ ion concentrations in extracellular fluids that result from the degradation of magnesium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we determined the in vivo antibacterial activity through evaluating the risk of bacteriuria. In comparison to permanent implant materials, the constantly degrading surface of JQ alloy could completely inhibit biofilm formation, and therefore reducing most of the complications related to peri-infections [ 7 , 17 ]. In an examination of antimicrobial activities of biodegradable magnesium based materials, Nguyen et al [ 19 ] identified several possible mechanisms of antimicrobial activity that may occur as a single activity or in tandem, including oxidative stress, interruption of quorum sensing processes, and changes in Ca 2+ ion concentrations in extracellular fluids that result from the degradation of magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…14%. Traditional permanent metallic ureteral stents can hardly get rid of the problems brought by biofilm formation due to the constant interface between stents and urine [ 7 , 10 ]. By contrast, magnesium ureteral stents represented by JQ stents are completely biodegradable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no significant correlation between the volume of encrustation and catheter-associated symptoms [25]. Yet, studies looked at the quantification of encrustations depending on the indwelling time, the differentiation of bacterial colonization, and risk factors associated with these processes [26][27][28][29]. Roupret et al found for ureteral stents with a mean indwelling time of 55.5 days a correlation between stone composition and catheter encrustation of over 70% [30].…”
Section: Risk Factors and Complications Of Encrustations On Stents An...mentioning
confidence: 99%
“… 5 As a result, it is considered that the formation of BF may be a key contributory factor to the relapse and intractability of urinary tract infections. 6 Therefore, the analysis of BF formation in patients with malignancy undergoing double J stent indwelling and the exploration of factors affecting urinary tract infection in patients are of great significance for clinical treatment. The results are reported as follows.…”
Section: Introductionmentioning
confidence: 99%